Sleep quality is inversely related to body mass index among university students - Wang,Jun (2019)
SUMMARY OBJECTIVE: The purpose of this study was to investigate the prevalence of overweight and obesity and its association with sleep quality in university students from the Anhui province in China. METHODS: A cross-sectional study was conducted in China with 1328 participants. The prevalence of underweight and obesity in university students was estimated according to the reference working group on obesity in China. The sleep quality was evaluated using the standard PSQI (Pittsburgh Sleep Quality Index). RESULTS: This study included 470 male and 858 female students from a university in Anhui; 4.4% of the females and 17.7% of the males were overweight or obese. The prevalence of obesity in males was significantly higher than in females, and the prevalence of obesity in higher years was greater than in other years (p<0.05). In general, the mean score for sleep quality was 4.91±2.67; 36.5% of male and 39.1% of female students had poor sleep quality (PSQI score >5). Among the seven components of sleep quality, sleep duration and the use of sleep medication showed significant differences between male and female students and different years (p<0.05). An obvious correlation was found between sleep quality and body mass index (BMI)(p<0.000) in females who took hypnotic drugs. CONCLUSION: This study suggests that the sleep quality of females is probably associated with their BMI. College students are a special group of young adults whose cause of poor sleeping quality and BMI may be significant to study, so the health status of university students can be improved.